2019
DOI: 10.1371/journal.pone.0211597
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel microRNA, miR-188, elevated in serum of muscular dystrophy dog model

Abstract: MicroRNAs (miRNAs) are non-coding small RNAs that regulate gene expression at the post-transcriptional level. Several miRNAs are exclusively expressed in skeletal muscle and participate in the regulation of muscle differentiation by interacting with myogenic factors. These miRNAs can be found at high levels in the serum of patients and animal models for Duchenne muscular dystrophy, which is expected to be useful as biomarkers for their clinical conditions. By miRNA microarray analysis, we identified miR-188 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Whether these above molecules can participate in age-related bone-muscle crosstalk or not requires further research. Furthermore, we were inspired to investigate whether miR-188, which appears increased in aging BMSCs, can be released through EVs to regulate aging muscle phenotype, since miR-188 was reportedly elevated in a muscular dystrophy dog model ( Li et al, 2015 ; Shibasaki et al, 2019 ). Zacharewicz et al (2014 , 2020) reported that miR-99b displays a negative age-dependent association with protein synthesis in skeletal muscle.…”
Section: Ev-micrornas Of Bone Cells Engaged In Bone-muscle Crosstalkmentioning
confidence: 99%
“…Whether these above molecules can participate in age-related bone-muscle crosstalk or not requires further research. Furthermore, we were inspired to investigate whether miR-188, which appears increased in aging BMSCs, can be released through EVs to regulate aging muscle phenotype, since miR-188 was reportedly elevated in a muscular dystrophy dog model ( Li et al, 2015 ; Shibasaki et al, 2019 ). Zacharewicz et al (2014 , 2020) reported that miR-99b displays a negative age-dependent association with protein synthesis in skeletal muscle.…”
Section: Ev-micrornas Of Bone Cells Engaged In Bone-muscle Crosstalkmentioning
confidence: 99%
“…Circulating exosomal miRNA in blood is linked to disease condition. For example, miR-126 and miR-223 are known markers of type 2 diabetes in human [49] and elevation of miR-188 in sera of muscular dystrophy dog [50]. Furthermore, adipose tissue is a major source of circulating exosomal miRNAs [38].…”
Section: Possible Roles In the Expansion Of Adipocytes In Tissues Thrmentioning
confidence: 99%
“…Canine X-linked muscular dystrophy in Japan (CXMD J ), a beagle-based dystrophic dog, is a midsize mammalian translational model of DMD ( Supplementary Fig. S1a) that mimics the human DMD phenotype more closely than the widely used dystrophin-deficient rodent models [13] and has been used to investigate molecular mechanisms triggering the physiopathological modifications in DMD [14][15][16][17][18][19]. The CXMD J dog model harbors a splice site mutation in intron 6 of the DMD gene on the X chromosome, which causes the loss of exon 7 and a disrupted reading frame in DMD mRNA (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%